2019
DOI: 10.1590/1981-6723.07918
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compound, nutritional and antioxidant profile of pollen collected by the genus melipona in North Eastern Brazil

Abstract: The pollen collected by eusocial bees is often reported as being healthy food due to its important nutritional and therapeutic properties. However, studies reporting such properties are rare, especially for pollen collected by the genus Melipona in northeastern Brazil, which is the focus of this research. Pollen from seven species of stingless bees was analysed for its nutritional composition (sugar, lipid, protein and amino acids). The phenolic compound profile was described based on fourteen phenolic compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…There had been several reports done on the amino acid contents in bee pollens, however, there is still a lack of information on free amino acids obtained in stingless bee propolis. According to de Oliveira et al (2019) , bee pollen collected from Melipona sp. contain leucine between 80 and 90 mg/g.…”
Section: Discussionmentioning
confidence: 99%
“…There had been several reports done on the amino acid contents in bee pollens, however, there is still a lack of information on free amino acids obtained in stingless bee propolis. According to de Oliveira et al (2019) , bee pollen collected from Melipona sp. contain leucine between 80 and 90 mg/g.…”
Section: Discussionmentioning
confidence: 99%
“…Bee pollens have rich phenolic compounds, flavonoids, phytosterols and other chemicals including vitamins and minerals with health protective potential (Denisow and Denisow-Pietrzyk 2016). Numerous studies have demonstrated that bee pollen has potential bioactive and therapeutic properties due to its healthy ingredients and these ingredients varies widely according to its botanical and geographical origin hence its therapeutic effects also vary (Oliveira et al 2019, Adaškevičiūtė et al 2019, Komosinska-Vassev et al 2015.…”
Section: Antioxidant Activity Of Bee Pollenmentioning
confidence: 99%